Experimental investigation on the effects of diesel and mahua biodiesel blended fuel in direct injection diesel engine modified by nozzle orifice diameters. (April 2018) - Vijay Kumar, M.; Veeresh Babu, A.; Ravi Kumar, P.
Abstract: In this paper, Mahua seed oil was transesterified with methanol using acid and alkaline catalyst process to obtain Mahua Methyl Ester. The chemical composition and physical properties of MME were tested. Experimental tests were investigated to study the performance, combustion and emission on computerized single cylinder CI diesel engine fueled with diesel and B20 (20% (vol.) of MME biodiesel + 80% (vol.) of diesel) along with each of the three nozzles has 3 injection holes, with the aperture of Ø = 0.20 mm (modified), Ø = 0.28 mm (base), and Ø = 0.31 mm (modified). The engine performance, combustion and emission is examined by measuring BSFC, BTE, In-cylinder pressure, MGT, HRR, CO, HC, NOx and smoke opacity. The authentic results were observed by using B20 and smaller orifice NHD. It is observed that smaller orifice NHD improves the air-fuel mixing, atomization, and vaporization which leads to shorter combustion duration. The B20 fuel showed better results such as performance at lower side of partial loads, combustion and emissions than the baseline diesel. The combination of B20 with smaller orifice NHD has shown appreciable results in performance, combustion and emissions. But, the only drawback was NOx is found to be increased. Highlights: The diesel engine is modified with each of the three nozzles has 3 injection holes, with the aperture of Ø = 0.20 mm (modified), Ø = 0.28 mm (base), and Ø = 0.31 mm (modified) and was tested with diesel and mahua biodiesel blended fuel. The plantation of mahua tree is very much essential in a future generation. The physical properties and chemical composition of biodiesel are seen to be more effective. The B20 with smaller orifices NHD are agreed to be more successful in combustion performance and emissions. During the process with B20 and smaller orifice NHD, it's implementing the NOx formation highly.